Degradation of paralytic shellfish toxins during flocculation of Alexandrium pacificum by an oxidized modified clay: A laboratory experiment - Song, Weijia; Song, Xiuxian; Shen, Huihui; Ding, Yu; Cheng, Ruihong; Yu, Zhiming (Ecotoxicology and environmental safety, 2023)
Paralytic shellfish toxins (PSTs), produced by Alexandrium pacificum in the marine environment, are a group of potent neurotoxins which specifically block voltage-gated sodium channels in excitable cells. During the toxigenic A. pacificum blooms outbreaks, PSTs can be accumulated through the food chain and finally enter the human body, posing a significant threat to human health and safety. This study experimented with a novel type of oxidized modified clay, potassium peroxymonosulfate modified clay (PMPS-MC), which could remove A. pacificum cells as well as reduce intracellular and extracellular PSTs toxicity rapidly. For the extracellular PSTs, its content decreased to below the detection limit rapidly through oxidative degradation within 15 min of 10 mg/L PMPS-MC treatment. Whereafter, although the residual cells in water column and some viable cells in flocculated sediment continued to secrete toxins, the extracellular PSTs content and toxicity in the PMPS-MC treatment groups remained significantly lower than those in the control group. For the intracellular PSTs, PMPS-MC might induce the transformation of more toxic GTX1&4 to less toxic GTX2&3 and C1&2, resulting in intracellular PSTs toxicity reduced within 15 min. In addition, intracellular PSTs content and toxicity in the PMPS-MC treatment groups were consistently lower than the control group within 48 h, possibly by inhibiting the A. pacificum cells growth. These results will provide a scientific basis for the field application of modified clay to control A. pacificum blooms. [Display omitted] •Effect of oxidized modified clay on paralytic shellfish toxins is firstly reported.•Oxidized modified clay could degrade above 90% of extracellular toxins in 15 min•Intracellular toxicity was reduced due to transformation of various toxins component.•Bacterial community was concerned for the variation of intracellular toxicity.